School-time Extension: Are the School Structure’s Hard Components Modified? Literature Review on the Subject - Vercellino, Soledad (2012)
For more than two decades we have witnessed in Latin America –in Argentina particularly– the development of policies to expand the school day. We understand that the implementation of such policies is an opportunity to observe the behavior of the school’s behavior faced with the attempt to modify one of its hardest components –school-time–; it becomes also a natural laboratory to analyze how much does the traditional organization of school-time can resist, how does it change and how do these changes (if implemented) impact the rest of the school components (spaces, groups, etc.). This paper shows the state of the art of the most significant studies in two research fields, in the context of primary education, on this matter: on the one hand, the studies related to organization and extension of school time and, on the other hand, research on the structural and structuring components of school-related aspects. The literature review indicates that studies on school-time and on the corresponding extension policies and programs do not report the difficulties found when trying to modify the hard components of the school system. Studies with the ‘school system’ as object of study have not approached the numerous school-time extension experiences, although time is one of the structural elements of the system.